Breast cancer screening: controversies and future directions. - Retsky M; Demicheli R; Hrushesky W; Retsky, Michael; Demicheli, Romano; Hrushesky, William (Current Opinion in Obstetrics & Gynecology, 2003)
Purpose Of Review: Recent criticisms of the mature breast cancer screening trials claimed that there is no evidence that screening saves lives. This has developed into a major public controversy, causing physicians, women, and policy analysts to rethink and debate mammography-screening guidelines. We have studied this subject from a different perspective -- using computer simulation to fit a simple growth model to clinical data. We can thus provide another viewpoint of the screening controversy that may help elucidate the underlying biology and aid policy makers in devising sound screening guidelines.Recent Findings: We agree with some reviewers that there is partial validity to the criticism. Based on our studies, we have arrived at a new explanation of why screening has not lived up to expectations.Summary: Our fundamental hypothesis is that breast cancers often undergo periods during which they are temporarily dormant. In addition, surgical intervention to remove primary tumors can interrupt this dormancy. Therefore screening finds smaller tumors with fewer positive lymph nodes, which is beneficial. But then the resulting extirpation accelerates the growth of dormant distant micrometastases, and results in earlier relapses than in women who have not been screened. This partly offsets the early detection advantage. One hypothetical mechanism proposed to explain this biology is that surgical wounding, particularly for premenopausal node-positive patients, can trigger the angiogenesis of dormant avascular micrometastases.